Studi Penjadwalan Pelaksanaan Proyek Rehabilitasi Bangunan Pelimpah (Spillway) Bendungan Pacal Kec. Temayang, Kab. Bojonegoro, Provinsi Jawa Timur Menggunakan Microsoft Project Manager 2016 - Prayogi, Anasrul Septian; Marsudi, Suwanto; Suprijanto, Heri (Fakultas Teknik, Universitas Brawijaya, 2021)
A project called success when viewed from an economic perspective, the project is carried out effectively and efficiently. In other word the project is avoided from all kinds of expenses that are not excluded, so that the planned benefits can be achieved. To achieve the results of a construction project that is efficient in terms of cost, time, and labor, the writer applies the Microsoft Project Manager 2013 program to help plan, manage, and schedule which strongly supports the project administration process. This study discusses scheduling and financing use 3 alternatives which include analysis of machine productivity, duration of the project, the resources requirement, analysis of labor unit prices, draft budgetary costs, and curve plans s taking into account the implementation of the work order and material requirements of scheduling Microsoft Project Manager 2016 that produces a network in the form of a giant chart. The purpose of this final assignment is to find out which alternative is the most efficient in terms of time and cost to accelerate the duration of the project. The three alternatives provide different analysis and results which are certainly different in terms of time and cost with alternative 1 (16 months, total project costs of Rp. 116.195.725.172,89), alternative 2 (14 months, total project costs of Rp. 114.977.966.202,28), and alternative 3 additions of heavy equipment (10 months, total project costs of Rp. 120.742.705.287,18). In terms of time and cost and the weaknesses of the three alternatives, it can be concluded that the addition of heavy equipment is an alternative that is considered efficient for implementation.